2021
DOI: 10.3389/fcvm.2021.713694
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cardiac Toxicity Induced by Cancer Therapies Requiring Intensive Care Unit Admission

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 146 publications
0
14
0
Order By: Relevance
“…Moreover, a clinical trial of anti-PD-1 antibody reported a positive response in PDAC patients with MMR alterations, although further studies in a larger patient cohort are needed [ 17 ]. Of note, many novel therapies have cardiac toxicity that need to be considered [ 62 , 63 , 64 , 65 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a clinical trial of anti-PD-1 antibody reported a positive response in PDAC patients with MMR alterations, although further studies in a larger patient cohort are needed [ 17 ]. Of note, many novel therapies have cardiac toxicity that need to be considered [ 62 , 63 , 64 , 65 ]…”
Section: Discussionmentioning
confidence: 99%
“…This led the Food and Drug Administration (FDA) to approve the drug Olaparib for patients with mCRPC who harbor mutation in BRCA1/BRCA2 and/or ATM genes. MMR-mutated patients can benefit from immunotherapy, with the FDA having recently approved PD-L1 inhibitor pembrolizumab (KEYTRUDA) for the treatment of patients with microsatellite instability-high (MSI-H)/MMR-deficient [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among chemotherapy drugs that are most likely to induce cardiotoxicity, anthracyclines (e.g., doxorubicin) have been used since the late 1950s to treat solid and hematologic cancers such as lymphoma, leukemia, sarcoma, and breast cancer. Anthracyclines are associated with several cardiovascular toxicities, including dilated cardiomyopathy with left ventricular systolic dysfunction leading to heart failure ( 59 ). In an Italian prospective study assessing more than 2,600 patients, the overall incidence of anthracycline-induced cardiotoxicity was 9% ( 60 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…Of note, a number of anti-HER2 agents are approved in HER2-positive breast [e.g., monoclonal antibodies, antibody-drug conjugates, and tyrosine kinase inhibitors (TKIs)] and gastric cancer (e.g., monoclonal antibodies, antibody-drug conjugates) ( 67 ). Among them, trastuzumab, a targeted therapy to the HER2 receptor in breast cancer and all its derivatives such as trastuzumab emtansine or trastuzumab deruxtecan, can be responsible for acute cardiac toxicity, which is usually reversible as opposed to the aforementioned anthracyclines ( 59 ). For patients receiving cardiotoxic chemotherapy, such as anthracycline or other anti-HER2 therapy, guidelines recommend a three-monthly left ventricular ejection fraction monitoring ( 68 ).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation